2020
DOI: 10.1021/acs.energyfuels.0c02270
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Evolution of the Fluid Effect of Multiple Reservoirs Due to CBM Coproduction: An Experimental Investigation

Abstract: Coalbed methane (CBM) coproduction in areas with multiple reservoirs has been an important means of improving gas production. The dynamic evolution of the fluid effect is not considered, which is a key factor leading to low production. To study coproduction mechanisms further and understand the evolution of the spatiotemporal characteristics of the dynamic fluid effect, a large-scale vertical well coproduction device was designed and the coproduction process was simulated. The results are as follows: (1) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Reservoir pressure is a key force to push CBM moving from wells in the exploitation process, which is an important factor affecting the production of CBM wells. Generally, in order to avoid the influence of in situ stress at different depths, pressure gradient is considered as an important indicator to measure reservoir pressure. , …”
Section: Occurrence Features Of Cbm Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reservoir pressure is a key force to push CBM moving from wells in the exploitation process, which is an important factor affecting the production of CBM wells. Generally, in order to avoid the influence of in situ stress at different depths, pressure gradient is considered as an important indicator to measure reservoir pressure. , …”
Section: Occurrence Features Of Cbm Resourcesmentioning
confidence: 99%
“…Generally, in order to avoid the influence of in situ stress at different depths, pressure gradient is considered as an important indicator to measure reservoir pressure. 1,72 The investigation by Zhang et al 73 on the pressure gradient in the Ordos, Qinshui, and San Juan basins show that Ordos and Qinshui both have subhydrostatic pressure gradients. Su et al 43 found that only the southern area of Qinshui Basin has high pressure, and the permeability is >1 mD (see Table 4).…”
Section: Occurrence Features Of Cbm Resourcesmentioning
confidence: 99%
“…23,24 Physical simulation experiments of multilayer coproduction were conducted, the influence mechanism of productivity between different production layers was preliminarily revealed, and an evaluation index of interlayer interference was put forward. [25][26][27] The evaluation and prediction of productivity used geochemical information from water produced from CBM wells. 28 To summarize, previous studies have focused on the geological background of multiseam CBM development and the simulation and evaluation of combined production capacity; however, they have not conducted research targeted at the problems that combined-layer drainage wells present, wherein they are generally unable to stabilize production, and the contribution of each production layer and the factors controlling productivity are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…According to the development engineering and productivity characteristics of combined‐layer drainage wells, there is no inevitable relationship between the fracturing effect and the in‐situ permeability of the coal reservoir, and the key lies in the reformability of the reservoir 23,24 . Physical simulation experiments of multilayer coproduction were conducted, the influence mechanism of productivity between different production layers was preliminarily revealed, and an evaluation index of interlayer interference was put forward 25–27 . The evaluation and prediction of productivity used geochemical information from water produced from CBM wells 28 …”
Section: Introductionmentioning
confidence: 99%
“…Coalbed methane (CBM) has become one of the most important yet unconventional gas resources because it is a clean energy source with a high calorific value. In recent years, the production and utilization of CBM in China have gradually increased. , In 2019, China’s CBM production was 88.8 × 10 8 m 3 . There are still great challenges in single-well production prediction and optimization owing to the lack of accurate understanding of the internal structure of coal reservoirs and gas–water two-phase flow behavior.…”
Section: Introductionmentioning
confidence: 99%